Validity and Practicality Test of Applied Mathematics Digital Teaching Materials for Blended Learning for Polytechnic Students - I Ketut Darma; I Gede Made Karma; I Made Anom Santiana (Politeknik Negeri Bali, 2021)
This study aims to determine the level of validity and practicality of teaching materials in the form of textbooks and digital student activity sheets (SAS) applied mathematics for blended learning models. Research using the 4D model development method includes: Define, Design, Develop, and Disseminate, carried out at the Politeknik Negeri Bali (PNB). The validity of textbooks and SAS is seen from the feasibility of: content, presentation, language and graphics. While practicality is seen from the ease of use, attractiveness of offerings and benefits. Data were collected through validation and practicality questionnaires, then analyzed descriptively. The results showed the level of validity of textbooks and SAS reached 83.1% and 83.7% were categorized as valid, while the practicality level reached 83.4% and 82.9% were valid categories. Applied mathematics digital teaching materials are suitable for blended learning, but small revisions are needed. The implication is that Draft II of applied mathematics digital teaching materials, its development after minor revisions can be continued to the effectiveness test, evaluation and dissemination stages.